SÍNTESE E CARACTERIZAÇÃO ESPECTROSCÓPICA DE BIOCOMBUSTÍVEL DE ÓLEO DE FRITURA - Voigt, Carmen Lúcia (2009)
This work have studied the biofuel sinthesys by acid etanolic transesterification, by using frying oil as raw material. Biofuel quality was monitored by volumetrics and spectroscopic techniques. The results indicated that the best yield, 94,5, was obtained by using the following conditions: 75C, 60 minutes and 2 mL of sulfuric as catalyst. 1H NMR spectra allowed determine the fatty acids biofuel profile at any times of reaction, as well the ethyl esters molecular weight, iodine and saponification value, and reaction yield. The biofuel support thermal stress at 110C/8h. Good correlations were obtained between: 1H NMR iodine values and that determined by the AOCS method; 1H NMR saponification values and that determined by the AOCS method; 1H NMR molecular weight with saponification values as determined by the AOCS method and absorbances at 247nm with peroxid values as determined by AOCS method, whose regression coefficients ranged from 0,961 to 0,976. 13C NMR spectroscopy has discriminated the components presents in rude and distilled biofuel. The biofuel quality can be monitored efficiently by espectroscopics techniques as 1H, 13C NMR and UV-Vis.